Pengaruh Pemahaman Wajib Pajak, Kesadaran Wajib Pajak dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak UMKM di Kota Semarang - Ilham Iftakukhoiri; Batara Daniel Bagana (Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this study is to evaluate and assess the impact of taxpayer comprehension, taxpayer awareness, and tax sanctions on compliance with MSME taxpayers in the city of Semarang. A qualitative technique was adopted for the research. Data gathering strategies included the distribution of questionnaires based on the study's criteria. Purposive sampling was utilized in this investigation. The study's findings indicate that Taxpayer Understanding, Taxpayer Awareness, and Tax Sanctions have a beneficial impact on MSME Taxpayer Compliance. It is desired that the Directorate General of Taxes would continue to improve the socialized of taxation among the general population, particularly MSME actors. This is done to promote taxpayers' comprehension and awareness of MSME actors' responsibilities to comply with applicable legislation.